ANALISIS JUAL BELI EMAS SECARA TIDAK TUNAI - Nuhbatul Basyariah (At-Tauzi : Jurnal Ekonomi Islam, 2020)
The purpose of this study is to analyze the sale and purchase of gold in a non-cash basis based on the basis of Islamic economics. This research is a descriptive qualitative research, with a literature study approach. Data were analyzed by inductive method. The results of the analysis show that buying and selling gold in cash is contrary to the syara' argument as the basis for Islamic economic practice. Based on the existing syara texts about the basic rules of buying and selling usury goods including gold, and the illat (legal background) of the prohibition of these objects is not stated in the text at all so that the illat cannot be taken. Therefore, gold buying and selling transactions must be carried out in cash, because the legal requirement of a gold sale and purchase transaction is that each exchanger must submit the goods in one assembly. Therefore, if each of the exchangers separates, while both have not delivered the goods, then the sale and purchase is invalid.